2019
DOI: 10.1002/cam4.2636
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pathological complete response by comparing MRI‐based radiomics pre‐ and postneoadjuvant radiotherapy for locally advanced rectal cancer

Abstract: BackgroundTotal mesorectal excision following neoadjuvant chemoradiotherapy (nCRT) is recommended in the latest treatment of locally advanced rectal cancer (LARC).ObjectiveTo predict whether patients with LARC can achieve pathologic complete response (pCR), comparing MRI‐based radiomics between before and after neoadjuvant radiotherapy (nRT) was performed.MethodsOne hundred and sixty‐five MRI‐based radiomics features in axial T2‐weighted images were obtained quantitatively from Imaging Biomarker Explorer Softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…In recent years, there was an increased interest in the field of radiomics for predicting the rectal cancer response to nCRT, with numerous research being conducted in this respect. The majority of studies focused on predicting the pathological complete response, using a single MRI sequence (T2-WI or apparent diffusion coefficient (ADC) maps) or a multiparametric approach [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Additionally, there are several studies that investigated the performance of radiomic features to discriminate good responders [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there was an increased interest in the field of radiomics for predicting the rectal cancer response to nCRT, with numerous research being conducted in this respect. The majority of studies focused on predicting the pathological complete response, using a single MRI sequence (T2-WI or apparent diffusion coefficient (ADC) maps) or a multiparametric approach [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Additionally, there are several studies that investigated the performance of radiomic features to discriminate good responders [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contrast-enhanced T1-WI sequence is not routinely included in the MRI protocol for rectal cancer staging. The potential of radiomics features extracted from MRI T2-weighted images for predicting a pathological complete response of rectal cancer was demonstrated in several recent studies, which reported promising results of their radiomics models with AUCs ranging from 0.69 to 0.93 [ 51 , 52 , 57 , 69 , 70 , 71 ]. In contrast to MRI, a recent study had demonstrated that radiomics features extracted from CT images showed no predictive power for complete pathological response in LARC [ 72 ], while another research showed that MRI T2-WI radiomics model performed better than CT radiomics model for predicting the LARC response to nCRT [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study believed that radiotherapy cannot improve survival for SCLLM patients as a whole. Nevertheless, it is meaningful to identify CRC patients who are sensitive to radiotherapy, as some other studies did [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It follows that the use of radiomics in the evaluation of LARC, as described above, might also allow identifying the responsive patients and providing them with targeted therapies while differentiating the non-responsive patients who could beneficiate of intensified neoadjuvant treatment regimen as neoadjuvant mFOLFIRINOX before nCRT [ 9 ]. More specifically, various authors have recently addressed the prediction of nCRT responses based on clinical assessments or different TRG staging systems [ 7 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, the first relevant distinction of the present study is that in all those studies, the ratio r was far smaller than that in the present study.…”
Section: Discussionmentioning
confidence: 99%